Ruhiyah Attachment: Integrating Spirituality into Attachment Theory for Enhanced Child Development - Astuti, Sriyati Dwi; Nurjannah, Nurjannah (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2024)
Purpose – This article aims to introduce a new perspective in attachment theory called ruhiyah attachment. Ruhiyah attachment emphasizes the role of caregivers as mediators to connect children spiritually with Allah SWT, proposing this spiritual connection as a potential solution to the mental health crisis among teenagers. Design/methods/approach – This paper employs a literature research methodology. The research involves (1) selecting the topic, (2) searching academic databases for relevant articles and journals, (3) collecting data from primary sources (articles and books on attachment theory) and secondary sources (application and implementation studies), (4) analyzing literature to identify patterns, themes, or differences across ten sources, (5) presenting findings, and (6) conducting a critical assessment of ruhiyah attachment as a new perspective in attachment studies. Findings – The research presents ruhiyah attachment as a new perspective in child attachment studies. It emphasizes that spiritual attachment, facilitated by caregivers as mediators, is crucial for children's development. Ruhiyah attachment extends beyond the mother-child bond to include a spiritual connection with the Creator, potentially addressing mental health crises by fostering a strong spiritual foundation in children. Research implications/limitations – This research broadens the discourse on child attachment studies. The literature review methodology allows a comprehensive examination of various perspectives in attachment research. Ruhiyah attachment offers a new viewpoint that may stimulate future studies. Limitations include the reliance on secondary sources and the need for empirical validation of the proposed perspective. Practical implications – Ruhiyah attachment can enhance early childhood education and care by integrating spirituality into attachment theory. This perspective allows children to develop a direct spiritual connection with Allah SWT through their bond with caregivers, promoting long-term mental and spiritual well-being. It suggests that spiritual strength can help prevent mental health crises and encourage moral development. Originality/value – This research introduces a spiritual dimension to child attachment studies, addressing the mental health crisis by proposing ruhiyah attachment as a novel perspective. Paper type Literature review